Antibiofilm effect of antimicrobials used in the therapy of mycobacteriosis. (October 2016) - Flores, Vanessa da Costa; Siqueira, Fallon dos Santos; Mizdal, Caren Rigon; Bonez, Pauline Cordenonsi; Agertt, Vanessa Albertina; Stefanello, Sílvio Terra; Rossi, Grazielle Guidolin; Campos, Marli Matiko Anraku de
Abstract: Rapidly growing mycobacteria (RGM) are opportunistic pathogens found in the environment. When in biofilms, mycobacteria is highly resistant to antibacterial treatments. The purpose of this study is to evaluate the antibiofilm activity of antimicrobials commonly used in therapy against mycobacteria. The antimicrobial susceptibility of Mycobacterium abscessus, Mycobacterium fortuitum and Mycobacterium massiliense was determined in planktonic and sessile populations. The antimicrobials amikacin, ciprofloxacin, clarithromycin, doxycycline, imipenem and sulfamethoxazole were tested. For each drug, it was evaluated the susceptibility of the pathogen, the ability to inhibit biofilm formation and the resistance of biofilms to antimicrobial activity. Results showed although, the antimicrobials tested are used as an alternative therapy for RGM, M. abscessus proved to be resistant to clarithromycin, beside that, M. massiliense showed a resistant profile to clarithromycin and sulfamethoxazole. Moreover, the inhibition of biofilm formation and its destruction have not been fully met. Considering that the biofilms are a known form of bacterial resistance, the failure of alternatives to inhibit or destroy biofilms can trigger the recurrence of infections. In RGM, besides causing treatment failures, biofilms are a factor of pathogenic risk, since these microorganisms are found in environmental sources and can cause infections easily. Highlights: Biofilms formed by rapidly growing mycobacteria (RGM) are resistant to antimicrobials commonly used in mycobacteriosis therapy. The development of biofilms is an important pathogenic risk factor once that cause failures in drug treatments.